2003
DOI: 10.1007/s00244-002-1140-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Lead-Contaminated Sediment to Mute Swans

Abstract: Most ecotoxicological risk assessments of wildlife emphasize contaminant exposure through ingestion of food and water. However, the role of incidental ingestion of sediment-bound contaminants has not been adequately appreciated in these assessments. This study evaluates the toxicological consequences of contamination of sediments with metals from hard-rock mining and smelting activities. Lead-contaminated sediments collected from the Coeur d'Alene River Basin in Idaho were combined with either a commercial avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
3
13
2
Order By: Relevance
“…This effect was also observed in previous studies with mallard ducklings experimentally exposed to Pb with sediment contaminated with Pb acetate (828 mg/g Pb dry weight; Hoffman et al, 2000), adult mute swans exposed to Pb contaminated sediment (700 mg/g Pb dry weight; Day et al, 2003) and mallard ducks with Pb contaminated food (1840 mg/g Pb dry weight; Mateo et al, 2003b). Alkaline phosphatase is an indicator of osteoblastic activity (Campbell, 1986), and Pb exposure has been associated with altered bone mineralization in birds (Gangoso et al, 2009).…”
Section: Plasma Biochemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…This effect was also observed in previous studies with mallard ducklings experimentally exposed to Pb with sediment contaminated with Pb acetate (828 mg/g Pb dry weight; Hoffman et al, 2000), adult mute swans exposed to Pb contaminated sediment (700 mg/g Pb dry weight; Day et al, 2003) and mallard ducks with Pb contaminated food (1840 mg/g Pb dry weight; Mateo et al, 2003b). Alkaline phosphatase is an indicator of osteoblastic activity (Campbell, 1986), and Pb exposure has been associated with altered bone mineralization in birds (Gangoso et al, 2009).…”
Section: Plasma Biochemistrysupporting
confidence: 86%
“…In the erythrocyte, O 2 · human epidemiological studies, which suggest that kidney function may be altered even at the lowest levels of PbB o 5 mg/dl (Ahamed and Siddiqui, 2007b). The decrease of ALT activity in plasma observed in coots has been reported previously in mute swans exposed to low Pb contaminated sediment (Day et al, 2003). However, increases of ALT have been reported in mallards exposed to high Pb levels, which can be related to hepatic alterations (Mateo et al, 2003a).…”
Section: Oxidative Stressmentioning
confidence: 84%
“…Waterfowl, in particular swans, appear predisposed to acute lead poisoning due to high marshland contamination with lead pellets and the feeding habits of the birds. Severe lead intoxication in birds results in neurologic impairment that can interfere with flight and ability to prehend food 10–12. Lead accumulates in lipid, with particularly high concentrations in myelin.…”
mentioning
confidence: 99%
“…Hoffman et al () reported that Pb from contaminated sediment in feed was 44% as available as Pb acetate in feed when fed to ducklings. Blood Pb concentrations were found to be greater when waterfowl were fed suboptimal diets (Hoffman et al ; Day et al ), possibly due to nutritional deficiencies, such as a reduced level of Ca (Scheuhammer ), or to a greater rate of ingestion. Compounds may bind Pb to soil and sediment; the addition of phosphoric acids to Pb‐contaminated sediments decreased the rate of absorption by subadult mallards (Heinz et al ; Furman et al ).…”
Section: Discussionmentioning
confidence: 99%